2019
DOI: 10.1093/rheumatology/kez295
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of rheumatic syndromes associated with checkpoint inhibitors therapy

Abstract: Compared with conventional cancer therapies, the spectrum of toxicities observed with checkpoint inhibitors is unique and can affect any organ system. Arthralgia and myalgia were by far the most commonly reported rheumatic immune-related adverse events in clinical trials, and there is now a growing number of case series and reports describing clinical features of de novo rheumatic immune-related adverse events, which will be the focus of this review. Some patients develop genuine classic rheumatic and musculos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…The median time from ICI initiation to symptom onset appears to be less than three months. Joint involvement has been evidenced after only one dose of ICIs but can also occur up to 2 years after immunotherapy, sometimes becoming chronic despite the cessation of ICIs [ 28 ].…”
Section: Rheumatic Immune-related Adverse Eventsmentioning
confidence: 99%
“…The median time from ICI initiation to symptom onset appears to be less than three months. Joint involvement has been evidenced after only one dose of ICIs but can also occur up to 2 years after immunotherapy, sometimes becoming chronic despite the cessation of ICIs [ 28 ].…”
Section: Rheumatic Immune-related Adverse Eventsmentioning
confidence: 99%
“…Median time to symptom onset following ICI initiation did not exceed the period of three months. Review of the literature, however, highlights the clinical variability of ICI-exposed patients developing arthritis [9,13]. In a recent review of case reports and case series [14], 90 cases of de novo ICI-related arthritis were identified in a period of 18 months.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
“…On the other hand, a de novo condition with features of myopathy/myositis has been described in recent years following ICI therapy in cancer patients [6,9,13]. The differentiation between paraneoplastic and ICI-induced myositis can be sometimes difficult [35].…”
Section: Myositismentioning
confidence: 99%
“…The impact of immunotherapy on the bone of patients with PCa has only begun to be explored. It is well established that immune checkpoint inhibitors result in immune‐related rheumatic and musculoskeletal adverse events, such as inflammatory arthritis, arthralgia, and myalgia 77,78 . Yet only recently has a study found that immunotherapies result in SREs.…”
Section: Discussionmentioning
confidence: 99%